The oxidation of styrene by chromium–silica heterogeneous catalyst prepared from rice husk - Adam, Farook; Mohamed Iqbal, Mohammad Anwar (Elsevier, 2010)
Chromium was incorporated into the silica matrix extracted from rice husk in basic, neutral and acidic medium. The prepared catalysts were labeled as RHCr-10, RHCr-7 and RHCr-3 according to their pH. The specific surface area of RHCr-10, RHCr-7 and RHCr-3 was determined to be 144, 143 and 564 m2 g−1, respectively. The XRD results showed the catalysts to be amorphous. RHCr-3 showed better catalytic activity with 99.92% conversion of styrene. Benzaldehyde was the major product with styrene oxide, phenyl acetaldehyde, acetophenone, 1-phenylethanol, phenylglyoxal, styrene glycol and benzoic acid as by-products. Leaching of chromium was minimal and RHCr-3 could be recycled several times.